Marxism and nationalism : theoretical origins of a political crisis - Nimni, Ephraim; Laclau, Ernesto (London : Pluto Press, 1991)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisme; communisme; nationalisme